A Critical Review on Lightweight Design of Battery Pack Enclosure for Electric Vehicles - Dhoke, Ashvin; Dalavi, Amol (http://dx.doi.org/10.31427/IJSTT.2021.4.2.2, 2021)
An electric vehicle battery pack which is a gathering of battery modules which subsequently comprised of the battery cell is a primary source of control transmission for an Electric Vehicle (EV). The inappropriate design of the battery enclosure will cause many genuine issues, such as cracking, causing noise, or battery harm. At the same time, the weight of the battery enclosure is huge; in order to get better the driving range of the electric vehicle and diminish the influence of the battery on the vehicle dynamic performance and acceleration performance, it is essential to carry out the lightweight design of the battery enclosure. This paper reviews the multi-material battery enclosure design optimization, the multi- technologies, and a proficient Battery Management System (BMS) for compact battery pack design used to lightweight battery pack enclosure design; the multi-objective optimization approach for distinctive parameters of battery pack enclosure design optimization by diverse manufacturing techniques.